Proposta de abordagem interdisciplinar de conceitos relacionados ao Sistema Solar para docentes do Ensino Médio - Pinto, Anna Paula de Alencar Lima (2020)
Astronomy enables the articulation of different areas of knowledge, providing the construction of integrated and contextualized knowledge. However, the subjects related to Astronomy are mainly worked in a superficial and or mistaken way due to the lack of adequate training of teachers and the lack of correct and updated teaching materials. Due to these factors, we investigate how to disseminate Astronomy in Basic Education through the continuous training of high school teachers. Besides, an educational product generated is an educational handbook containing conceptual approaches from the Solar System theme, indicating how these can be worked in a correct, playful andthe interdisciplinary way in the disciplines of History, Biology, Physics, Geography and Portuguese Language. In this research, the following didactic games were also proposed and used: Historical and Solar Trail, Astrobiological Roulette, Game of the three Astrophysical tracks and Bing of the Planets. It was also realized a short course of six hours class, distributed in two meetings of three hours each. Seventy-four teachers participated in this training that sought to aggregate the conceptual dimensions with teaching practices mediated by educational games, helping them to arouse curiosity and student interest in the topics covered. As results obtained, it is emphasized that besides to the effectiveness of the intended scientific dissemination that also contributes to foster the realization of continuous teacher training to work on Astronomy from an interdisciplinary perspective.